PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS IV SDN 3 KERTASURA - Caswati Caswati (Universitas Negeri Medan, 2022)
Abstract: Energy sources are one of the learning materials that must be mastered by elementary school students. Many benefits are generated from the material, but students have not obtained it optimally because the average student score is less than the KKM. The other influence is the use of the learning model that is applied is not appropriate. This study aims to determine the effect of the Make a Match cooperative learning model on student learning outcomes in science subjects in grade IV at SDN 3 Kertasura. In this study using a quasi-experimental method. The population of this study were all fourth grade students at SDN 3 Kertasura with a total of 40 students, of which 20 samples of class IVa as the experimental class and 20 samples of class IVb as the control class. Data analysis was carried out quantitatively. Quantitative analysis was carried out through the t-test with a significance level of 0.05 or 5%, meaning that if the significance value of tcount > ttable states Ha is accepted and Ho is rejected, it means that there is a significant effect between the independent variable and the dependent variable. Based on the processed data, it was found that the cooperative learning model of Make a Match type had a significant effect on student learning outcomes in the Make a Match type of cooperative learning in class IV at SDN 3 Kertasura. Keywords: Learning Outcomes, Make a Match Type Cooperative Learning Model, Grade IV Elementary School. Abstrak: Sumber energi merupakan salah satu materi pembelajaran yang wajib di kuasai siswa SD. Banyak manfaat yang dihasilkan dari materi tersebut, namun siswa belum memperolehnya dengan maksimal karena rata-rata nilai siswa kurang dari KKM. Adapun pengaruh lainya yaitu penggunaan model pembelajaran yang diterapkan kurang tepat. Penelitian ini bertujuan mengetahui pengaruh model pembelajaran Kooperatif tipe Make a Match terhadap hasil belajar siswa pada mata pelajaran IPA di kelas IV SDN 3 Kertasura. Pada penelitian ini menggunakan metode kuasi eksperimen. Populasi penelitian ini seluruh siswa kelas IV SDN 3 kertsura dengan jumlah 40 siswa yang mana 20 Sampel kelas IVa sebagai kelas eksperimen dan 20 sampel kelas IVb sebagai kelas kontrol. Analisis data di lakukan secara kuantitatif. Analisis kuantitatif dilakukan melalui uji t dengan taraf signifikansi ∞ 0,05 atau 5% artinya apabila nilai signifikansi thitung > ttabel menyatakan Ha diterima dan Ho ditolak, artinya terdapat pengaruh yang signifikan antara variabel bebas dengan variabel terikat. Berdasarkan olahan data diperoleh temuan, bahwa model pembelajaran kooperatif tipe Make a Match berpengaruh secara signifikan terhadap hasil belajar siswa pada mata pelajaran Kooperatif tipe Make a Match di kelas IV SDN 3 Kertasura. Kata Kunci : Hasil Belajar, Model Pembelajaran Kooperatif Tipe Make a Match, kelas IV SD.